Dental implants in patients with ectodermal dysplasia: a computer guided quad zygomatic case report and literature review - Arcuri, Lorenzo (2023)
Ectodermal dysplasia (ED) is a genetic disorder affecting anatomical structures with an ectodermal origin. The consequent alveolar bone anomalies and lack of teeth require a multidisciplinary approach to rehabilitate patients function and esthetics. To avoid bone grafting procedures the application of zygomatic implants was suggested for the upper jaw treatment. The advancements in three-dimensional (3D) radiology and the introduction of digital implant planning software could enhance the approach to zygomatic implants in ED patients. The present case report describes the quad zygomatic implant treatment of the edentulous maxilla of an ED patient by means of computer guided implant surgery. The patient reported previous failure of bone grafting procedures in the upper jaw. The implants were immediately loaded with a screw-retained complete-arch resin prosthesis. The patient was followed up for 1 year with no biological nor mechanical complications reported, but a slight bone resorption in the anterior zone was observed. Zygomatic implants could be a potential alternative treatment to bone grafting in upper jaw and the digital implant planning could enhance the surgical procedure.